Path Learning in Individuals With Down Syndrome: The Challenge of Learning Condition and Cognitive Abilities - Meneghetti, Chiara; Toffalini, Enrico; Lanfranchi, Silvia; Roch, Maja; Carretti, Barbara (Frontiers in Psychology, 2021)
Analyzing navigational abilities and related aspects in individuals with Down syndrome (DS) is of considerable interest because of its relevance to everyday life. This study investigates path learning, the conditions favoring it, and the cognitive abilities involved. A group of 30 adults with DS and 32 typically-developing (TD) children matched on receptive vocabulary were shown a 4 x 4 Floor Matrix and asked to repeat increasingly long sequences of steps by walking on the grid. The sequences were presented under two learning conditions, one called Oral instructions (participants received verbal instructions such as “turn right” or “turn left”), the other Observation (participants watched the experimenter’s moves). Participants were also assessed on verbal and visuospatial cognitive measures. The results showed a similarly better performance in both groups when the Floor Matrix task was administered in the Observation as opposed to the Oral instructions condition. As for the relation with cognitive abilities, in the Floor Matrix task in the Oral instructions condition, individuals with DS showed an effect of both verbal and visuospatial abilities, which was only positive for verbal ability. The effect of verbal and visuospatial abilities was negligible in the TD group. In the Observation condition, performance was predicted by sequential working memory in both groups. Overall, these results shed light on path learning in individuals with DS, showing that they benefited from the Observation condition, and that the involvement of their cognitive abilities depended on the learning condition.